A Quantitative Analysis of Microcirculation in Skin Defects Covered with Topical Wound Dressings or a Newly Developed Collagen Matrix. (November 2017) - Held, Manuel; Medved, Fabian; Petersen, Wiebke; Tolzmann, Dascha Sophie; Rahmanian-Schwarz, Afshin; Schaller, Hans-Eberhard; Rothenberger, Jens
ABSTRACT: OBJECTIVE: Innovative skin substitutes and temporary wound dressings are frequently used in the treatment of superficial and partial-thickness wounds. The aim of this study was to compare 2 commonly used temporary skin dressings with a newly developed collagen matrix to determine changes in microcirculation as measured by blood flow, hemoglobin oxygenation, and relative hemoglobin values during healing of partial-thickness skin defects. METHODS: This animal study involved 28 adult male Lewis rats. On the back of each rat, 2 standardized partial-thickness skin defects were generated through a skin dermatome (n = 56). Then, wounds were treated with polylactide-based copolymer skin substitute (Suprathel, PolyMedics, Denkendorf, Germany; n = 14), biosynthetic skin dressing (Biobrane, Smith & Nephew, Hamburg, Germany; n = 14), or Collagen Cell Carrier (CCC; Naturin Viscofan, Weinheim, Germany; n = 14). The remaining control wounds were left untreated (n = 14). MAIN OUTCOME MEASURES: Perfusion dynamics were assessed every 10 days for 80 days with the O2C device (LEA Medizintechnik, Gieβen, Germany) to determine blood flow, hemoglobin oxygenation, and relative amount of hemoglobin. MAIN RESULTS: Blood flow was increased in all wounds for at least 30 days after wound generation. The relative amounts of hemoglobin were increased in superficial layers (2 mm) for 10 to 20 days. Hemoglobin oxygenation in the superficial layers decreased in the polylactide-based copolymer skin substitute and biosynthetic skin dressing–treated groups and initially increased in the untreated wounds and CCC groups on day 10; these values also decreased. CONCLUSIONS: The presented results demonstrate the complex changes in microcirculation in the course of healing partial-thickness wounds with different wound dressings and contribute to a better understanding of these wounds. However, based on the results of the study, a clear recommendation for a specific substitute is not yet possible.